Insights for transformation of contaminants in leachate at a tropical landfill dominated by natural attenuation - Yin, Ke (2016)
The purpose of this study was to track the long-term trends of contaminants distribution in the old landfill of Singapore through monitored natural attenuation and to explore the main parameters that rule such transition. Contaminants distribution, including dissolved organic matter (DOM), inorganic species, heavy metals, and organic compounds, was investigated via monitoring wells in the years 1997, 2004 and 2011. The data revealed that the distribution of contaminants possessed selective attention of spots associated with leachate movement. The hydrogeology of the landfill governed the fate and transportation of contaminants. More specifically, strong statistical correlations were identified between DOM and certain constituents in the leachate, suggesting enhanced mobilization potential. However, the leachate composition exhibited limited correspondence to the nearby solid waste, indicating the minor effect induced by the partitioning coefficient. The presence of sulphate unveiled air intrusion, suggesting increased stability of the landfill, where enhanced biodegradation occurred at earlier period responsible for higher BOD removal. Afterwards other parameters continued to facilitate the compounds removal resulting in overall low concentrations of the contaminants.